Locus of Control and Academic Achievement in Higher Education: A Bibliographic Review - Carlos Alberto Mayora-Pernía; Nelly Fernández de Morgado (Universidad Nacional, Costa Rica, 2015)
The purpose of this paper is to provide a bibliographic review about the relation between locus of control (LC) and academic achievement in higher education students. Online repositories were the main source of information. The most important findings show that, (a) the LC construct has evolved from being a dichotomist to a multidimensional variable; (b) there are very few recent international studies and none of them covers Latin-America; (c) interdisciplinary research is scarce and the absence of the qualitative approach is noticeable; and, (d) whether direct or indirectly, most studies show a relation between LC and academic achievement in higher education. These findings show the need to address this topic in Latin America. It is suggested to conduct interdisciplinary, longitudinal, qualitative, and quantitative studies under the supervision of institutions and teachers; the results would be used to design interventions to improve que quality of education.